Associations of Lipid-related SNPs with Circulating Phylloquinone Are Proportional with Triglycerides (P15-008-19). (13th June 2019) - Kelly, Jennifer; Dashti, Hassan; Ordovas, Jose M; Matuszek, Gregory; Smith, Caren; Huggins, Gordon; Booth, Sarah
Abstract: Objectives: Phylloquinone is transported on triglyceride-rich lipoproteins. Preliminary evidence from a genome-wide association meta-analysis suggests that genetic variants that influence triglycerides (TGs), such as rs964184 at the APOA1/C3/A4/A5 gene cluster, also influence circulating phylloquinone. To further evaluate this overlap, we examined the linear relationship between a weighted TG genetic risk score (wTG-GRS) with circulating phylloquinone. Methods: We constructed a wTG-GRS comprised of 20 SNPs that were previously associated with TGs in a genome-wide association meta-analysis for blood lipids ( n  > 188, 000 individuals of European ancestry). The assigned weights corresponded to the effect-sizes (β) reported for each SNP's association with TGs. With meta-analytic summary statistic data from a separate genome-wide association meta-analysis of circulating phylloquinone ( n  = 2138 individuals of European ancestry), a statistical technique was used to approximate the linear association of the wTG-GRS with circulating phylloquinone. A p-value of 0.05 for the estimate was considered statistically significant. First, the estimate was calculated without adjustment for TGs using Model 1 summary statistics, then calculated with adjustment for TGs using Model 2 summary statistics. Results: The estimate for the linear association of the wTG-GRS with circulating phylloquinone was significant without and with adjustment for TGs (Model 1: β = 0.052, P  = < 0.0001, Model 2: β = 0.027, P  = 0.0001, respectively). The goodness-of-fit of the model was improved from Model 1 (p-het = 0.022) to Model 2 (p-het = 0.054). Conclusions: The associations of TG-related SNPs with circulating phylloquinone were proportional to their associations with TGs. This provides further evidence of the shared genetic links between TGs and phylloquinone and suggests genetic studies of vitamin K should consider TGs. Funding Sources: Study supported by the USDA Agricultural Research Service under Cooperative Agreement No. 58-1950-7-707 and NHLBI T32HL069772.